Eisenmenger syndrome in pregnancy: experience from a tertiary care centre - Chaturvedi, Nidhi; More, Hetal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Eisenmenger syndrome first described by Victor Eissenmenger is the end stage of a long-standing congenital left -right shunt, characterised by reversal of shunt, pulmonary hypertension and heart failure. Pregnancy with its haemodynamic changes, in these women is contraindicated due to high risk of poor maternal and foetal outcome, as stated by WHO and is considered for termination. However, if pregnancy is continued, management requires intense monitoring and multidisciplinary approach in a resource intense centre. Present article describes the clinical presentation, management and outcome of three pregnant women with Eisenmenger syndrome in a tertiary care centre in Rajasthan. All three women presented in late pregnancy for the first time. Two had a known congenital defect but were non-compliant with their treatment and follow up. They were unaware of the risks of pregnancy in their condition. One woman was diagnosed for the first time in pregnancy. All women delivered by emergency Caesarean Delivery due to complications. However maternal and foetal outcome was good in all three women and they were discharged in stable condition. Counselling regarding the need for regular follow up and avoidance of pregnancy was done at the time of discharge. Eisenmenger syndrome poses a significant challenge in pregnancy with high risk of complications to both mother and foetus. Favourable outcome may be achieved with advanced cardio- obstetric team in a well-equipped centre. However, counselling regarding avoidance of pregnancy or regular antenatal care must be impressed upon in young women with congenital heart defects.